Collage made from Leaf Dry for Instilling the Value of Cooperation - Aprilana Humola; Tri Mulyanny Uloli; Melsi Alinda Karim; Futriwin B. Lunggela; Abdul Rahmat (Periodica Journal, 2022)
Liability answer means a obligation give answer which is calculation on all things that happened and obligations for give recovery on losses it may incur and have _ nature very high level of care and honesty whereas work same is something activities that have different levels _ start from exists coordination and cooperation until occur inside collaboration _ something activity work same . In activity this we have To do analysis situation or observation at SDN 10 Kota Barat. Analysis condition SDN 10 Kota Barat is physically divided be 2 floors that is floors 1 and 2. Floor 1 is available a number of room study that is room class 1, 2, 3, 4 along with operator room, teacher room and room head school . Floor two , there grade 5 and grade 6 and there a number of room other . Collage made from base leaf dry generally made for children so they can develop intelligence naturalist and capable categorize or capable recognize what types of flora and fauna just what 's around it as well as could push they for could manage and use it leaf dry .
Keywords: Learning; Cooperation; Collage